Word frequencies and lexical richness in L2 writing : a study on Finnish learners of English from different levels - Ratamo, Ilari (My University, 2024)
In this MA thesis three different levels of Finnish learners of English were studied to find to whether or not their improvement as English learners could be seen in different lexical measures. These measures concentrated on vocabulary depth and lexical richness. The first aim was to find out how proficiency affects the frequencies of words used in written text. In addition, also academic language use was tracked. The second aim of the study is to find out to what degree does lexical variation and lexical density reveal differences in learners of English. The groups were comprehensive school, high school and university students. From each group around fifty essays were collected and treated in order to make them work with vocabulary analysers that were used to study the data. Two different analysers were used, one for word frequencies, EAP, and one for lexical variation and density, VP-Classic. The results of the study suggest that the usage of word frequencies does differ between proficiency levels and can be used as a predictor to vocabulary development. As the proficiency improves, the more likely the learner is to use less common language. As for lexical variation and density, they did not seem to reveal differences between proficiency groups. Out of six different relations between the groups across these two variables, only one was significantly different and all the results were extremely similar. In future studies topic selection should be thought through with serious caution and the raw data should be treated with great care to ensure the validity of the results.
Keywords: word frequency, lexical density, lexical variation, vocabulary, vocabulary analyser, English as a foreign language, vocabulary depth